Molecular Structure Investigation, Spectroscopic Characterization, UV Spectral Analysis and Optical Band Gap Determination of (2E)-3-(3-Bromo- 4methoxyphenyl)-1-(pyridin-2-yl) prop-2-en-1-one A Food Preservative Chalcone (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
FT-IR and FT-Raman spectra of food preservative molecule (2E)-3-(3-Bromo-4methoxyphenyl)-1-(pyridin-2-yl) prop-2-en-1-one (PYR) were recorded and analyzed. The equilibrium geometry, various bonding and harmonic vibrational wave numbers have been calculated with the help of density functional theory (DFT) method. The assignments of the vibrational spectra have been carried out with the help of Normal coordinate analysis (NCA) following the scaled quantum chemical force field (SQMF) methodology. The natural bond orbital (NBO) analysis was carried out to reveal the nature of different interactions responsible for the electron delocalization and the charge transfer between the orbital's (\(n\)-\(π^*\), \(n\)-\(σ^*\), \(π\)-\(π^*\)). Blue shifting of (36 cm\({}^{-1}\)) C-H stretching mode provides the spectral evidence for the intermolecular interactions of C-H...Br. The optical transmittance provides a way to find the band gap which is determined using Taue plot.